(untitled) (Research, Society and Development, 2021)
Immunobiological drugs or biopharmaceuticals are defined as drugs in which the active substance is of biological origin, whose action is in specific points, which can be used in rheumatic, neurological, gastroenterological diseases, among others. In this sense, the present study aimed to describe, based on the literature, the importance of biopharmaceuticals and their applications in the treatment of immunological diseases. The searches were carried out in the BVS and SciELO libraries, and in the PUBMED database. In the field of data search, the following descriptors were used: “biological products/biological products” and “autoimmune disease/autoimmune diseases”. The inclusion criteria were free literature, available in English and Portuguese from 2011 to 2021, and duplicate and paid exclusions. Nineteen studies were selected, among which 3 immunological diseases were found, namely: rheumatoid arthritis, crohn and psoriasis and 9 types of biopharmaceuticals were identified, namely: abatacept, adalimumab, Certolizumab pegol, Etanercept, Golimumab, Infliximab, Rituximab, Tocilizumab and Secukinumab. Biopharmaceuticals are relatively new on the market and are still unknown by many patients, so it is important for a health professional who has knowledge of knowledge of both immunobiological and synthetic drugs, because the pharmacist is the professional who performs the dispensing and administration of these medications. Through this research, it is clear that, unlike many synthetic drugs that have a chemical structure not found in the human body, biological drugs are structurally similar to human compounds, which favors an increase in the potential to cure these diseases.